TRANSFORMASI LITERASI SAINS MELALUI SIMULASI LANGIT DIGITAL: STUDI PADA MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Golden R.S.C Ayomi; Aisyah Ali; Sarah Ohee (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Scientific literacy is an essential competency for prospective elementary school teachers in designing meaningful learning experiences based on scientific reasoning. However, many PGSD students still experience difficulties in explaining scientific phenomena, assessing investigation designs, and interpreting data or evidence, especially on astronomical topics that are abstract and prone to misconceptions. This study aims to evaluate the effectiveness of using the planetarium software Stellarium in improving students' scientific literacy on the topics of Earth's rotation, revolution, and lunar phases. The method used was a quasi-experimental pretest–posttest design in two whole-class groups, where the experimental group received dynamic visual simulation-based learning using Stellarium, and the control group followed conventional learning. The results showed that the experimental group had significantly higher scientific literacy scores than the control group (mean 74.49 vs. 64.84; p = 0.010; g ≈ 1.23). The strongest effects occurred in the subprocesses of “explaining phenomena” (g ≈ 1.42) and “interpreting data/evidence” (g ≈ 1.50), while “assessing/designing investigations” showed moderate improvement (g ≈ 0.76). Qualitative data from reflections and interviews confirmed a conceptual shift from common misconceptions (e.g., the causes of seasons or lunar phases) to a coherent, model-based understanding evidenced by visualizations from the simulation. These findings suggest that the use of Stellarium not only improved conceptual accuracy but also strengthened students' ability to connect observations, models, and evidence to explain astronomical phenomena. This study concludes that visual simulation-based learning such as Stellarium is effective in improving the scientific literacy of elementary school teacher (PGSD) students. Implications include the need for systematic integration of evidence-based digital media into the Earth and Space Science curriculum to address misconceptions and strengthen prospective teachers' scientific reasoning skills.